The effects of lettuce extract on the level of T4, memory and nerve conduction velocity in male rats - Majid Jafari Nejad Bajestani; Mahdi Yousefi; Mousa-; Seyed Mahmoud Hosseini; Ali Taghipour; Shiba Yousefvand; Hamid reza Ghorbanzadeh (Mashhad University of Medical Sciences, 2020)
Objective: According to the traditional medicine,lettuce can affect nerve conduction velocity and memory. So, to investigate the effect of lettuce seeds extract on body activities, lettuce seeds were used. Materials and Methods: In the present study, the effects of lettuce (Lactuca sativa) seeds extract consumption (in drinking water) on T4 level, animals' weight, water and food consumption, nerve conduction velocity (NCV), and memory in Wistar rats, were investigated. In this study, 24 Wistar rats were used, and divided into three groups: control, L 200 mg/kg, and L 400 mg/kg. Results: The results showed that, the T4 level, food and water intake, time spent and distance travelled in Q1, delay time to enter and the number of entrance into the dark room in both treated groups were not significantly different from the control group. Animal weight and NCV, in 400 mg/kg group were not significantly different from the control group, but in 200 mg/kg group, they were significantly decreased (p<0.05). The duration spent in  the dark room (48 hr after shock) in L 400 mg/kg increased compared to the control group (p<0.05), but in L 200 mg/kg group at all time points, and in L 400 mg/kg treated group 3 and 24 hr after shock, it was not significantly different from the control group. Conclusion: Based on these findings, the T4 level, memory, food and water intake were not changed by lettuce extract, while NCV and animal weight were decreased following treatment with lettuce extract.